Топографический портрет Киева: жанровая специфика текста Н. Лескова “Печерские антики” - Dzyk, Roman; Chervinska, Olha (Ústav slavistyky Filozofické fakulty Masarykovy university, 2020)
The article under discussion is dedicated to the text by N. Leskov “Pechersky Antics” (1882), which has been very superficially studied by today’s literary critics. Apart from a few phrases regarding the idea of this work by N. Leskov himself (the letter to F. Ternovsky of 20.08.1882), the article analyzes some conclusions of well-known researchers concerning the genre peculiarities of N. Leskov’s creative activities. The concept, suggested by the author of the article, interprets the text as a quite specific genre form of a literary novel, which is fastened together into a systemic centripetal combination of diverse and colorful images, rather than the spontaneous arbitrariness of the narrated stories of individual “antics”, due to a single Kyiv chronotope (the opening of Tsepnoy Bridge).
Topographic Portrait of Kiev: Genre Peculiarities of N. Leskov’s Text "Pechersky Antics"
Keywords: Н.Лесков; «Печерские антики»; хронотоп; киевский текст; жанр; жанровый метаморфизм; лирический роман; N. Leskov; "Pechersky Antics"; chronotope; Kyiv text; genre; genre metamorficality; lyrical novel